RoboCup 2001. - Lima, P.
RoboCup 2001, the fifth international RoboCup competition was held in the United States. This article discusses, in detail, each one of the events at RoboCup-2001 with a focus on leagues with real robots. As an overview of the complete RoboCup-2001, and as an introduction to this article, we provide a short description of the RoboCup-2001 events
Keywords: RoboCup competitions; Humanoid; Mobile robots; Multiple agent systems; Multiple robot systems; Real-time control